Minimally Invasive Nasal Sampling in Children Offers Accurate Pneumococcal Colonization Detection. Issue 11 (November 2019) - Nikolaou, Elissavet; Blizard, Annie; Pojar, Sherin; Mitsi, Elena; German, Esther L.; Reiné, Jesús; Hill, Helen; McNamara, Paul S.; Collins, Andrea M.; Ferreira, Daniela M.; Jochems, Simon P
Abstract : Nasopharyngeal colonization of potential respiratory pathogens such as Streptococcus pneumoniae is the major source of transmission and precursor of invasive disease. Swabbing deeply the nasopharynx, which is currently recommended by World Health Organization, provides accurate pneumococcal detection but is unpleasant. We showed that nasal lining fluid filter strips offer equal detection sensitivity.